The Influence of Organizational Environment, Welfare, and Entrepreneurship on Productivity of SMEs In Makasar City - Asyari; Amiruddin Mise; Andi Pallawagau (CV ODIS, 2026)
This research aims to determine the influence of the organizational environment, employee welfare, and entrepreneurial orientation on productivity in MSMEs in Makassar City. The method used is quantitative descriptive research. The sampling technique was carried out randomly and proportionally to 100 MSMEs. Data collection techniques use observation, interviews, documentation, and questionnaires. Test data analysis using multiple linear regression tests. Partial T test, F model test, and R-squared coefficient of determination test. Based on the research results, it shows partially that the organizational environment influences work productivity, employee welfare influences work productivity, and entrepreneurial orientation influences work productivity, simultaneously influencing work productivity. The magnitude of the influence of the organizational environment, welfare, and entrepreneurial orientation on work productivity is 70%, while the remainder is contributed by other variables outside the independent variables used in this research.